Genomic characterization of a new phage BUCT541 against Klebsiella pneumoniae K1-ST23 and efficacy assessment in mouse and Galleria mellonella larvae - Pu, Mingfang; Li, Yahao; Han, Pengjun; Lin, Wei; Geng, Ronghua; Qu, Fen; An, Xiaoping; Song, Lihua; Tong, Yigang; Zhang, Shuyan; Cai, Zhen; Fan, Huahao (Frontiers in Microbiology, 2022)
Over the last decades, the spread of multi-drug-resistant-Klebsiella pneumoniae (MDR-KP) is becoming a new threat and new effective therapies against this pathogen are needed. Bacteriophage (phage) therapy is considered to be a promising alternative treatment for MDR-KP infections compared with antibacterial drug usage. Here, we reported a new phage BUCT541 which is able to lyse MDR-KP ST23. The genome of BUCT541 is a double-stranded linear 46,100-bp long DNA molecule with 48% GC content through the Next generation sequencing (NGS) data. A total of 81 open reading frames and no virulence or antimicrobial resistance genes are annotated in the BUCT541 genome. BUCT541 was able to lyse 7 of the 30 tested MDR-KP according to the host range analysis. And the seven sensitive strains belonged to the Klebsiella pneumoniae (K. pneumoniae) K1-ST23. BUCT541 exhibited high thermal stability (4-70 °C) and broad pH tolerance (pH 3-11) in the stability test. The in vivo results showed that BUCT541 (4 × 105 plaque-forming units (PFU)/each) significantly increased the survival rate of K. pneumoniae infected Galleria mellonella from 5.3% to 83.3% within 48 h. Moreover, in the mouse lung infection model, high doses of BUCT541 (2 × 107 PFU/each) cured 100% of BALB/c mice that were infected with K. pneumoniae. After 30 h of treatment with phage BUCT541 of multiplicity of infection (MOI) =10, the K. pneumoniae in the lungs of mice was lower than 104 CFU/mL, compared to the control group 109 CFU/mL. Together, these findings indicate that phage BUCT541 holds great promise as an alternative therapy with excellent stability and wide lysis range for the treatment of MDR-KP ST23 infection.